Unlocking the values of Artificial Intelligence (AI) in Human Resource Management (HRM) in enhancing employee retention / Maryam M. Azeem … [et al.] - M. Azeem, Maryam; Febriyanto, Ugik; Nurhadi, Ferrani Adinda; Halid, Hafinas (2023)
Human Resource management (HRM) is increasingly adopting Artificial Intelligence (AI) due to its potential to create value for consumers, employees, and organizations. Furthermore, employee turnover is a critical issue for organizations, resulting in high training costs and uncertainty. Recent studies indicate that organizations have yet to experience the anticipated benefits of AI adoption for employee retention. This study investigates the value of AI in HRM practices within organizations with a significant impact on employee retention. Poor candidate selection, a lack of training and career development opportunities, inadequate performance evaluation, and inadequate monitoring of employee engagement all contribute to high turnover rates. The paper emphasizes the importance of addressing these issues and the role of Artificial Intelligence (AI) in enhancing human resource practices in order to increase employee retention. AI techniques, such as machine learning and big data analysis, provide effective methods for predicting employee turnover, optimizing recruitment processes, boosting employee engagement, and undertaking sentiment analysis. By incorporating AI into HR practices, organizations can mitigate turnover issues and cultivate a more positive work environment, resulting in increased employee retention.